A forma e o contexto: testes experimentais da camuflagem de ninhos em duas espécies de aves da Mata Atlântica - Martins, Cassiano Bueno (Universidade Federal de São Carlos, 2025)
The Atlantic Forest is one of the most diverse and threatened ecosystems on earth, harboring a rich avifauna of great ecological relevance. Despite the remarkable bird diversity, substantial knowledge gaps on their reproductive aspects still persist, particularly on the antipredatory strategies. Nest predation is the main cause of avian reproductive failure, representing one of the strongest selective pressures molding their biology. Such pressure influences both nest-site selection and nest design, reducing the probability of detection by predators. Among antipredator strategies, camouflage stands out as a central mechanism to decrease the conspicuousness of nests and eggs, especially against visually oriented predators. Although most studies have focused on species that lay their eggs directly on the ground, the camouflage function of nests built on the vegetation, a common pattern among passerines, remain poorly explored. Moreover, the distinct modes of nest detection, i.e. visual or olfactory, suggest that different predator types impose specific selective pressures on nest form, material, and placement. In this context, this thesis is composed of two independent chapters, each designed to test, through field experiments, the camouflaging function of nests from two bird species of the Atlantic Forest. In the first chapter we investigated whether the “tail” of the blue manakin (Chiroxiphia caudata) nests acts as disruptive camouflage, reducing detection by visually oriented predators. The results showed that tailless nests were preyed upon about ten times more frequently than those with tails, and all recorded predation events were caused by visual predators, highlighting the functional role of the “tail” in decreasing nest detectability. In the second chapter, we evaluated whether the ornamentation of lateral branches and tail in nests of the white-throated spadebill (Platyrinchus mystaceus) function as an extended phenotype with a camouflaging role. Although no significant difference in predation rates was found between ornamented and non-ornamented nests, the consistent pattern of material addition and the resemblance to the surrounding substrate suggest a potential adaptive function of camouflage. Together, these results reinforce the importance of camouflage as an evolutionary force shaping the design and placement of tropical bird nests. They also highlight that ornamental feature, such as the “tail” of Chiroxiphia caudata nests and the decoration around Platyrinchus mystaceus nests may represent functional components of nest architecture, resulting from natural selection mediated by visual predation.
Form and context: experimental tests of nest camouflage in two bird species from the Atlantic Forest
Keywords: fenótipo estendido; predação; estratégias antipredatórias; experimentos; camuflagem disruptiva; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA DE ECOSSISTEMAS; 15. Vida Terrestre